The right to life in armed conflict - Park, Ian David, 1973- (Oxford : Oxford University Press, 2018)
What place does the right to life have in armed conflicts? And does it lock down military objectives? In the first sustained coverage of the area, Ian Park examines conflicts in Iraq, Afghanistan, Libya, and Syria to explicate how far governments should be entitled to derogations from human rights whilst engaging in combat operations.
This edition previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 5, 2018).
Keywords: Humanitarian law; Right to life; Law; International law